RESILIENSI PADA REMAJA BERDASARKAN KEUTUHAN KELUARGA - Amira Yasin; Gian Sugiana Sugara; Aam Imaddudin (Journal of Innovative Counseling : Theory, Practice, and Research, 2020)
The purpose of this study was to determine the picture of resilience in class XI SMK Mitrabatik, based on gender, family integrity and planning a program to increase student resilience. This study uses a quantitative descriptive method to reveal a picture of student resilience, the population in this study is class XI SMK Mitrabatik, amounting to 350 students, the technique in this study uses saturated sampling by making the population members a sample. The results of this study in general the resilience of class XI students at SMK Mitrabatik are in the category of resilience quite 49% (172 people), the highest aspect is the optimism aspect and the lowest aspect is the emotional regulation aspect. Based on gender and family integrity did not have a significant difference. The shortcomings of this study sample is still limited so it does not yet represent all students in SMK Mitrabatik.